Some questions of the principle of integrity of human beings in criminal trial. (Journal of actual problems of jurisprudence, 2016)
Ensuring the rights of the personality is especially actual in the sphere of criminal trial as in this sphere of imperious activity of government bodies essential restrictions and even violations constitutional the right of the personality arise and are shown. Here application of various measures of criminal procedure coercion, including measures of restraint which significantly limit the rights and legitimate interests of the personality, involved in the sphere of criminal justice is possible. Protection of human rights, its legitimate interests has to become the main and main objective of criminal trial. Andonly then through a prism of this task it is necessary to perceive interest of society and the state, consisting in providing a due law and order. Fight against crime is carried out first of all not for ensuring stability of a political regime in the country and tranquillity of society. Main goal of this fight is protection of the citizen and society against illegal encroachments, ensuring the rights and freedoms of each person, whose rights were struck by a crime.
Keywords: personality; rights and freedoms of the person; inviolability; immunity; integrity of human beings; etc.